Effect of the synthetic cannabinoid HU-210 on quorum sensing and on the production of quorum sensing-mediated virulence factors by Vibrio harveyi - Soni, Divya (BMC Microbiol, 2015)
BACKGROUND: Bacterial populations communicate through the cell density-dependent mechanism of quorum sensing (QS). Vibrio harveyi, one of the best studied model organisms for QS, was used to explore effects of the synthetic cannabinoid HU-210 on QS and different QS-regulated physiological processes in bacteria. RESULTS: Analysis of QS-regulated bioluminescence in wild-type and mutant strains of V. harveyi revealed that HU-210 affects the autoinducer-2 (AI-2) pathway, one of three known QS cascades of V. harveyi. Furthermore, QS-mediated biofilm formation and swimming motility in the mutant strain BB152 (AI-1(−), AI-2(+)) were significantly reduced in the presence of HU-210. HU-210 inhibited QS-mediated virulence factor production without any inhibitory effect on bacterial growth. It also alters the expression of several genes, which are regulated by QS, specifically downregulating the genes of the AI-2 QS cascade. CONCLUSION: First evidence is being provided for interference of bacterial signal-transduction systems by a synthetic cannabinoid. The effect of HU-210 was specific to the AI-2 cascade in V. harveyi. AI-2 is known as a "universal autoinducer" and interference with its activity opens a broad spectrum of applications for synthetic cannabinoids in future research as a potential anti-QS agent. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-015-0499-0) contains supplementary material, which is available to authorized users.